Prinsip Ekstrateritorial Dalam Penegakan Hukum Persaingan Usaha - Asti Rachma Amalya (Lembaga Penelitian dan Pendidikan Mandala, 2020)
Economic globalization has led to trade liberalization, many countries embracing a free market where trade and investment are carried out across national borders. As a consequence the boundaries between countries have disappeared, trade and investment restrictions have also declined and the potential for unfair business competition has increased. For this reason, each country seeks to provide protection for its citizens in its territorial territory and bring about conflicts between jurisdictions. The regulations governing the prohibition of monopolistic practices and unfair business competition do not explicitly regulate the application of extraterritorial principles in Indonesia, but KPPU has handled several cases involving foreign business actors and imposed sanctions on business actors who are not domiciled in Indonesia and against acts committed outside of Indonesia. One of the KPPU's decisions stated the Temasek Holdings business group and its subsidiaries had been proven guilty of violating the provisions of Article 27 of the Law on the Prohibition of Monopolistic Practices and Unfair Business Competition and that the KPPU had imposed sanctions. This paper will discuss the application of extraterritorial principles in the context of business competition in Indonesia and see considerations in the relevant KPPU decisions. It will also examine legal obstacles and challenges in the execution of executions because of regulations that have not explicitly governed the application of extraterritorial principles.